Conditioned effects of ethanol on the immune system. Issue 7 (April 2017) - Gano, Anny; Pautassi, Ricardo Marcos; Doremus-Fitzwater, Tamara L; Deak, Terrence
Several studies indicate that the immune system can be subjected to classical conditioning. Acute ethanol intoxication significantly modulates several pro-inflammatory cytokines (e.g. interleukins-1 and 6 [IL-1β and IL-6, respectively] and tumor necrosis factor alpha [TNFα])) in several brain areas, including amygdala (AMG), paraventricular nucleus (PVN), and hippocampus (HPC). It is unknown, however, whether cues associated with ethanol can elicit conditioned alterations in cytokine expression. The present study analyzed, in male Sprague-Dawley rats, whether ethanol-induced changes in the central cytokine response may be amenable to conditioning. In Experiments 1 and 2, the rats were given one or two pairings between a distinctive odor (conditional stimulus, CS) and the post-absorptive effects of a high (3.0 or 4.0 g/kg, Experiments 1 and 2, respectively) ethanol dose. Neither of these experiments revealed conditioning of IL-6, IL-1β, or TNFα, as measured via mRNA levels. Yet, re-exposure to the lemon-odor CS in Experiment 1 significantly increased C-Fos levels in the PVN. In Experiment 3, the rats were given four pairings between an odor CS and a moderate ethanol dose (2.0 g/kg), delivered intraperitoneally (i.p.) or intragastrically (i.g.). Re-exposure to the odor CS significantly increased IL-6 levels in HPC and AMG, an effect only evident in paired rats administered ethanol i.p. Overall, this study suggests that ethanol exposure can regulate the levels of IL-6 at HPC and AMG via classical conditioning mechanisms. These ethanol-induced, conditioned alterations in cytokine levels may ultimately affect the intake and motivational effects of ethanol. Impact statement: This study examines, across three experiments, whether odor cues associated with ethanol exposure can condition changes in cytokine expression. The analysis of ethanol-induced conditioning of immune responses is a novel niche that can help understand the transition from social drinking to alcohol abuse and dependence. Ethanol-induced conditioning of the immune system could likely exacerbate neuroinflammation and drug-related toxicity, which in turn may facilitate further engagement in ethanol intake. The main new finding of the present study was that, after four pairings of ethanol's unconditioned effects and a distinctive odor, the latter CS increased IL-6 levels in HPC and AMG. This suggests that ethanol's effects upon IL-6 in HPC and AMG may come under conditioned control, particularly after repeated pairings between distinctive odor cues and ethanol's effects. This article advances our knowledge of conditioned increases in cytokine responses, which should help understand the mechanisms underlying alcohol use, abuse, and relapse.